2017
DOI: 10.1007/s00592-017-0970-5
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive impairment and dementia: a new emerging complication of type 2 diabetes—The diabetologist’s perspective

Abstract: Type 2 diabetes mellitus (T2D) and Alzheimer's disease (AD) are two of the most common diseases of aging around the world. Given the frequency with which T2D and AD occur, the notion that people with T2D may be at increased risk for AD has large societal consequences, and understanding the mechanistic links between these diseases is imperative for the development of effective AD prevention and treatment strategies. Apart from being an accelerator of AD, T2D is associated with a progressive cognitive decline. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
110
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 151 publications
(113 citation statements)
references
References 45 publications
1
110
0
2
Order By: Relevance
“…Numerous epidemiological studies have demonstrated that individuals with type 2 diabetes have a significantly higher risk of developing neurodegenerative diseases, in particular, Alzheimer’s disease [81]. The retina is ontogenically brain-derived tissue, so it may provide an easily accessible and non-invasive way of examining CNS pathology.…”
Section: Retinal Neurodegeneration Is a Biomarker Of Neurodegenerativmentioning
confidence: 99%
See 2 more Smart Citations
“…Numerous epidemiological studies have demonstrated that individuals with type 2 diabetes have a significantly higher risk of developing neurodegenerative diseases, in particular, Alzheimer’s disease [81]. The retina is ontogenically brain-derived tissue, so it may provide an easily accessible and non-invasive way of examining CNS pathology.…”
Section: Retinal Neurodegeneration Is a Biomarker Of Neurodegenerativmentioning
confidence: 99%
“…Therefore, it could be postulated that, in individuals who develop brain neurodegeneration, a neurodegenerative process co-occurs in the retina (‘the eye as a window of the brain’). In fact, both diabetes-induced retinal neurodegeneration and Alzheimer’s disease share several pathogenic pathways, such as insulin signalling impairment, low-grade inflammation, the accumulation of advanced glycation end-products (AGEs) and an increase in oxidative stress [81]. In addition, several pathogenic pathways triggered in the brain of those with neurodegenerative diseases have also been found to be triggered in the retinas of individuals with type 2 diabetes [82].…”
Section: Retinal Neurodegeneration Is a Biomarker Of Neurodegenerativmentioning
confidence: 99%
See 1 more Smart Citation
“…Intensive research efforts in preclinical models have provided numerous hypotheses about the interaction between insulin resistance and neurodegeneration through a plethora of pathways. There is not enough evidence to provide specific recommendations to prevent the cognitive decline in individuals with or at high risk of type 2 diabetes [80]. …”
Section: Discussionmentioning
confidence: 99%
“…Exclusion of patients with diabetes and atrial fibrillation, frequently associated with high blood pressure, reduce the power of detecting small, but clinically relevant, effects. In fact, both diabetes and atrial fibrillation amplify the impact of blood pressure load on cerebrovascular risk and dementia . However, on clinical grounds, our task is to prevent cerebrovascular complications without too much care of which is the most relevant of the many coexisting patient risk factors.…”
mentioning
confidence: 99%